(untitled) (Resolusi: Jurnal Sosial Politik, 2026)
Modernizing public services in the digital age requires strengthening e-government, especially in order to enable efficient and long-lasting governance. The purpose of this study is to examine how artificial intelligence (AI) functions in e-government systems, with a focus on sustainable development. A rigorous literature review of several government papers, international policy reports, and scholarly journals is the approach taken. The study’s findings show that AI can enhance government governance, reduce budget abuse, increase access to public services, and improve bureaucratic efficiency. But issues like cybersecurity and the digital divide continue to be barriers. The efficiency of AI use in e-government is also influenced by the availability of infrastructure, laws, and human resources.